Variations in end‐of‐life care practices in older critically ill patients with COVID‐19 in Europe. (22nd April 2022) - Wernly, Bernhard; Rezar, Richard; Flaatten, Hans; Beil, Michael; Fjølner, Jesper; Bruno, Raphael R.; Artigas, Antonio; Pinto, Bernardo B.; Schefold, Joerg C.; Kelm, Malte; Sigal, Sviri; van Heerden, Peter V.; et al.
Abstract: Background: Previous studies reported regional differences in end‐of‐life care (EoLC) for critically ill patients in Europe. Objectives: The purpose of this post‐hoc analysis of the prospective multicentre COVIP study was to investigate variations in EoLC practices among older patients in intensive care units during the coronavirus disease 2019 pandemic. Methods: A total of 3105 critically ill patients aged 70 years and older were enrolled in this study (Central Europe: n = 1573; Northern Europe: n = 821; Southern Europe: n = 711). Generalised estimation equations were used to calculate adjusted odds ratios (aORs) to population averages. Data were adjusted for patient‐specific variables (demographic, disease‐specific) and health economic data (gross domestic product, health expenditure per capita). The primary outcome was any treatment limitation, and 90‐day mortality was a secondary outcome. Results: The frequency of the primary endpoint (treatment limitation) was highest in Northern Europe (48%), intermediate in Central Europe (39%) and lowest in Southern Europe (24%). The likelihood for treatment limitations was lower in Southern than in Central Europe (aOR 0.39; 95% confidence interval [CI] 0.21–0.73; p = 0.004), even after multivariable adjustment, whereas no statistically significant differences were observed between Northern and Central Europe (aOR 0.57; 95%CI 0.27–1.22; p = 0.15). After multivariable adjustment, no statistically relevant mortality differences were found between Northern and Central Europe (aOR 1.29; 95%CI 0.80–2.09; p = 0.30) or between Southern and Central Europe (aOR 1.07; 95%CI 0.66–1.73; p = 0.78). Conclusion: This study shows a north‐to‐south gradient in rates of treatment limitation in Europe, highlighting the heterogeneity of EoLC practices across countries. However, mortality rates were not affected by these results. Abstract :